Differences in Cortisol Response to Trauma Activation in Individuals with and without Comorbid PTSD and Depression - Dekel, Sharon; Ein-Dor, Tsachi; Rosen, Jeffrey B.; Bonanno, George A. (Frontiers in Psychology, 2017)
Background: Although depression symptoms are often experienced by individuals who develop posttraumatic stress disorder (PTSD) following trauma exposure, little is know about the biological correlates associated with PTSD and depression co-morbidity versus those associated with PTSD symptoms alone. Methods: Here we examined salivary cortisol responses to trauma activation in a sample of 60 survivors of the World Trade Center attacks on September 11, 2001. Participants recalled the escape from the attacks 7 months post 9/11. Salivary cortisol levels were measured before and after their recollection of the trauma. PTSD, depression, and somatic symptoms were also assessed. From the behavioral assessment scales, the participants were grouped into three conditions: those with comorbid PTSD and depressive symptoms, PTSD alone symptoms, or no-pathology. Results: Baseline and cortisol response levels differed between the comorbid, PTSD alone, and no-pathology groups. Individuals endorsing co-morbid symptoms had higher PTSD and somatic symptom severity and their cortisol response decreased following their trauma reminder while a trend of an elevated response to the trauma was found in the PTSD alone group. Our findings show distinct psychological and biological correlates related to the endorsement of PTSD with and without depression comorbidity. Conclusions: The findings suggest that comorbidity symptoms manifestation entails a separate trauma induced condition from PTSD. Future research on biological correlates of comorbid PTSD and depression is warranted.